EFFECTIVENESS OF SUPERVISION WITH COMPLIANCE WITH NURSING ROUND DOCUMENTATION IN THE CHILD CARE ROOM - Ita bagus argentina; Aris suprianto; Tri Ratna Ningsih (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Nursing rounding is conducted every two hours, which includes monitoring patient complaints, monitoring IV line complaints, positioning the patient comfortably, meeting personal needs, meeting elimination needs, and maintaining privacy. In-service conditions, nurses' compliance with nursing rounding documentation remains low. Compliance with nursing rounding documentation can be improved through nurse supervision. This study aims to analyze the relationship between supervision and compliance with nursing rounding documentation. This study used a correlational analytical approach with a cross-sectional method. A sample of 84 nurses was selected using purposive sampling from a population of 90 nurses. The instruments used included a nursing rounding documentation observation questionnaire, GROW-ME coaching, and a compliance observation sheet. Data analysis was performed using the Spearman Rho correlation test. Most nurses received good supervision (89%). Eighty percent of nurses demonstrated compliance with nursing rounding documentation. There was a significant relationship between supervision and nursing rounding documentation (p=0.000). Nurse supervision significantly increased compliance with nursing rounding documentation. It is recommended that institutions strengthen coaching, training, and motivation programs to improve the quality of documentation and overall nursing care.